The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1002/hbm.23411
|View full text |Cite
|
Sign up to set email alerts
|

Neuroticism modulates brain visuo-vestibular and anxiety systems during a virtual rollercoaster task

Abstract: Different lines of research suggest that anxiety-related personality traits may influence the visual and vestibular control of balance, although the brain mechanisms underlying this effect remain unclear. To our knowledge, this is the first functional magnetic resonance imaging (fMRI) study that investigates how individual differences in neuroticism and introversion, two key personality traits linked to anxiety, modulate brain regional responses and functional connectivity patterns during a fMRI task simulatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 97 publications
2
47
0
2
Order By: Relevance
“…Specifically, we observed that greater right hemisphere dominance was associated with lower anxiety, whereas increased anxiety was found in less right hemisphere dominant individuals. Our results highlight the interplay between vestibular processing and anxiety networks (Riccelli et al., ), but also implicate the importance of hemispheric lateralisation upon influencing these systems.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Specifically, we observed that greater right hemisphere dominance was associated with lower anxiety, whereas increased anxiety was found in less right hemisphere dominant individuals. Our results highlight the interplay between vestibular processing and anxiety networks (Riccelli et al., ), but also implicate the importance of hemispheric lateralisation upon influencing these systems.…”
Section: Discussionsupporting
confidence: 75%
“…The link between anxiety and the vestibular system that are both vital processes in balance control was initially described in the 19th century (Gowers, ). Since then, a close interaction of these two systems has been highlighted (Balaban, Jacob, & Furman, ; Riccelli et al., ; Staab, Balaban, & Furman, ; Viaud‐Delmon, Venault, & Chapouthier, ). Examples of such reciprocal influences include previous findings which demonstrate that patients suffering from vestibular dysfunction are at higher risk of developing anxiety disorders compared to healthy individuals(Best, Eckhardt‐Henn, Tschan, & Dieterich, ), and that following an acute unilateral vestibular loss, outcome is most aptly predicted by the patients anxiety level and bodily vigilance status(Cousins et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, an introverted, dependent, and anxious personality is a potential risk factor for the development and negative course of PPV . Patients with a personality of high resilience and optimism are less likely to develop persistent dizziness after an acute vestibular disorder, whereas personality traits such as neuroticism and introversion influence brain responses to vestibular and visual stimuli on visual‐vestibular‐anxiety systems . We found task‐dependent hyperconnectivities within brain networks regulating various aspects of emotional behavior and interoceptive pathways in PPV patients (Fig.…”
Section: Discussionmentioning
confidence: 75%
“…. Moreover, fMRI data during simulated vertigo suggest an association between psychological traits and functional connectivity patterns within visuo‐vestibular and anxiety‐related cortical networks, but the directionality of this association remains unclear. Our findings highlight (1) the importance of early identification of abnormal visual dependency and concurrent anxiety in VN and (2) the potential for early treatments to improve long‐term outcome by reducing visual dependency (sensory reweighting strategies) and combining pharmacotherapy and cognitive therapies to reduce anxiety and autonomic arousal.…”
Section: Discussionmentioning
confidence: 99%